The response of Trauma & Orthopaedic Departments to the first four weeks of lockdown for the COVID-19 pandemic – A trainee-led analysis of the East of England. Issue 1 (February 2021) - ,; Tansey, Rosamond J.; Patel, Jaison; Sanghrajka, Anish; Ngu, Albert; Liew, Ignatius; Rooney, Aaron; Matthews, William; Sadique, Hammad; Begum, Rumina; Al-Sukaini, Ahmad; Barwell, Jennifer; et al.
Abstract: Through a trainee research collaborative, we have studied the changes in practice of 12 T&O departments across the East of England over the first four weeks of the UK lockdown and COVID-19 pandemic, comparing to activity levels with the corresponding period in 2019. We focused on changes in T&O practice, training and redeployment of Trainees. Units differ considerably in several aspects of practice. We found a 97% reduction in elective operating, 64% reduction in elective outpatient activity and 37% reduction in operative trauma. 58% of trainees continued working in T&O clinics, with an average of 6 operative cases over this period. Our modelling suggests that the impact on training will persist; counter-measures must be incorporated into central recovery planning. Highlights: The early response to the COVID-19 situation in Trauma and Orthopaedics. COVID-19 impact on Orthopaedic services. Recovery planning and impact on training secondary to COVID-19.